1991
DOI: 10.1007/bf00788970
|View full text |Cite
|
Sign up to set email alerts
|

The Ryle Marital Patterns Test as a predictor of symptoms of anxiety and depression in couples in the community

Abstract: The associations between marital relationships, as measured by the Ryle Marital Patterns Test, and symptoms of anxiety and depression as measured by the Interval General Health Questionnaire (I-GHQ), were assessed in 98 married couples in the community. Logistic regression analyses showed that symptoms of anxiety and depression in wives were best predicted by low ratings of affection exchange. Occupational class interacted with husbands' affection ratings, suggesting that in the nonmanual class only lower affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…Our findings for depression support the results of the meta-analysis of Mathews & Reus (2001), who found little, but significant, marital resemblance for affective disorders. The finding of marital resemblance for anxiety symptoms in this study confirms various earlier reports in both clinical and population-based studies (Tambs, 1991 ;Zimmermann-Tansella & Lattanzi, 1991 ;McLeod, 1995 ;Galbaud du Fort et al 1998 ;Maes et al 1998 ;Dubuis-Stadelmann et al 2001), reporting correlations between 0.1 and 0.3 using either diagnostic or dimensional ratings of anxiety. Two studies did not find marital resemblance for anxiety disorders.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings for depression support the results of the meta-analysis of Mathews & Reus (2001), who found little, but significant, marital resemblance for affective disorders. The finding of marital resemblance for anxiety symptoms in this study confirms various earlier reports in both clinical and population-based studies (Tambs, 1991 ;Zimmermann-Tansella & Lattanzi, 1991 ;McLeod, 1995 ;Galbaud du Fort et al 1998 ;Maes et al 1998 ;Dubuis-Stadelmann et al 2001), reporting correlations between 0.1 and 0.3 using either diagnostic or dimensional ratings of anxiety. Two studies did not find marital resemblance for anxiety disorders.…”
Section: Discussionsupporting
confidence: 91%
“…Findings for depressive and anxiety disorders, however, are not unequivocal. For anxiety disorder, some studies found no evidence of increased risk of anxiety disorder in spouses of patients with an anxiety disorder (Eagles et al 1987 ;Low et al 2007), but several other studies found an increased risk (Tambs, 1991 ;Zimmermann-Tansella & Lattanzi, 1991 ;McLeod, 1995 ;Galbaud du Fort et al 1998 ;Dubuis-Stadelmann et al 2001), with spousal correlations varying between 0.1 and 0.3. Only one study mentioned data on marital resemblance for obsessive-compulsive disease (OCD).…”
Section: Introductionmentioning
confidence: 99%